Stable‐isotope probing of the polycyclic aromatic hydrocarbon‐degrading bacterial guild in a contaminated soil - Maiysha D. Jones; Douglas W. Crandell; David R. Singleton; Michael D. Aitken (Environmental Microbiology, 2011)
Summary The bacteria responsible for the degradation of naphthalene, phenanthrene, pyrene, fluoranthene or benz[ a ]anthracene in a polycyclic aromatic hydrocarbon (PAH)‐contaminated soil were investigated by DNA‐based stable‐isotope probing (SIP). Clone libraries of 16S rRNA genes were generated from the 13 C‐enriched (‘heavy’) DNA recovered from each SIP experiment, and quantitative PCR primers targeting the 16S rRNA gene were developed to measure the abundances of many of the SIP‐identified sequences. Clone libraries from the SIP experiments with naphthalene, phenanthrene and fluoranthene primarily contained sequences related to bacteria previously associated with the degradation of those compounds. However, Pigmentiphaga ‐related sequences were newly associated with naphthalene and phenanthrene degradation, and sequences from a group of uncultivated γ‐ Proteobacteria known as Pyrene Group 2 were newly associated with fluoranthene and benz[ a ]anthracene degradation. Pyrene Group 2‐related sequences were the only sequences recovered from the clone library generated from SIP with pyrene, and they were 82% of the sequences recovered from the clone library generated from SIP with benz[ a ]anthracene. In time‐course experiments with each substrate in unlabelled form, the abundance of each of the measured groups increased in response to the corresponding substrate. These results provide a comprehensive description of the microbial ecology of a PAH‐contaminated soil as it relates to the biodegradation of PAHs from two to four rings, and they underscore that bacteria in Pyrene Group 2 are well‐suited for the degradation of four‐ring PAHs.